Identifying and assessing students with emotional disturbance - Tibbetts, Terry J. (Paul H. Brookes Publishing Co, 2013)
To help improve social and academic outcomes for all students, school psychologists must be ready to accurately identify, assess, and support students with emotional disturbance. This essential resource gives them the clear information, practical guidance, and up-to-date research they need. Ideal for use as a supplemental textbook or a key reference for in-service school psychologists, this book will clarify what constitutes emotional disturbance in educational settings, how it differs from the clinical definition, and how to assess and intervene effectively so students learn and thrive. PREPA.